2014
DOI: 10.1242/jcs.158915
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear pore targeting of the yeast Pom33 nucleoporin depends on karyopherin- and lipid-binding

Abstract: Pom33 is an integral membrane protein of the yeast nuclear pore complex (NPC), required for proper NPC distribution and assembly. To characterize Pom33 NPC-targeting determinants, we performed immunoprecipitation experiments followed by mass spectrometry analyses. This identified a novel Pom33 partner, the nuclear import factor Kap123. In vitro experiments revealed a direct interaction between Pom33 C-terminal domain (CTD) and Kap123. In silico analysis predicted the presence of two amphipathic α-helices withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
36
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 53 publications
0
36
0
Order By: Relevance
“…Furthermore, the membranes surrounding the nuclear pore have high curvature similar to that of ER tubules (Mészáros et al, 2015). POM33 (TU:TO 3.81; TU:BL 3.79) may provide additional linkage between nucleus biogenesis and ER tubules, as it has also been implicated in the nuclear pore complex distribution and NE remodeling (Casey et al, 2015; Chadrin et al, 2010; Floch et al, 2015). The localization of POM33 and its homologous proteins (PER33, Tts1, and TMEM33) can be explained by the presence of multiple TMHs and APHs and their interactions with known tubule proteins, including Rtn1p, Sey1p, and Lnp1p (Casey et al, 2015; Chadrin et al, 2010; Zhang and Oliferenko, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the membranes surrounding the nuclear pore have high curvature similar to that of ER tubules (Mészáros et al, 2015). POM33 (TU:TO 3.81; TU:BL 3.79) may provide additional linkage between nucleus biogenesis and ER tubules, as it has also been implicated in the nuclear pore complex distribution and NE remodeling (Casey et al, 2015; Chadrin et al, 2010; Floch et al, 2015). The localization of POM33 and its homologous proteins (PER33, Tts1, and TMEM33) can be explained by the presence of multiple TMHs and APHs and their interactions with known tubule proteins, including Rtn1p, Sey1p, and Lnp1p (Casey et al, 2015; Chadrin et al, 2010; Zhang and Oliferenko, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…All other integral membrane nucleoporins are not essential, but generally only a single one can be absent. It has also been shown that targeting of Pom33, an integral membrane nucleoporin, to the NPC requires its amphipathic helices, which preferentially bind to highly curved membranes (12). Also implicated in NPC biogenesis are the reticulons, which are able to induce membrane curvature and have been shown to be important for the formation of tubule structures of the ER (40).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, many NPC proteins, including yeast Nup85, Nup120, and Nup133, contain amphipathic helical ALPS (ArfGAP1 lipid-packing sensor) motifs that sense lipid packaging at the curved membranes of the POM (11). Thus, a complex array of lipid-protein interactions is thought to stabilize the highly curved pore membranes, but the roles of these interactions in membrane fusion and curvature are not fully understood (12,13).…”
mentioning
confidence: 99%
“…Rapid transportin-dependent import of Nup153 might prevent its membrane association outside of the nucleus. We wondered whether transportin interaction could also directly affect Nup153 membrane binding similar to Kap123, which regulates membrane interaction of the spindle body component Nbp1p and the C-terminal domain of the transmembrane nucleoporin Pom33p in yeast (Floch et al, 2015;Kupke et al, 2011). To test this, the N terminus of Nup153 was employed in liposome flotation assays after pre-incubation with transportin.…”
Section: Transportin Regulates Nup153 Membrane Interactionmentioning
confidence: 99%